Fast absolute 3D CGO-based electrical impedance tomography on experimental tank data. (30th December 2022) - Hamilton, S J; Muller, P A; Isaacson, D; Kolehmainen, V; Newell, J; Rajabi Shishvan, O; Saulnier, G; Toivanen, J
Abstract: Objective. To present the first 3D CGO-based absolute EIT reconstructions from experimental tank data. Approach. CGO-based methods for absolute EIT imaging are compared to traditional TV regularized non-linear least squares reconstruction methods. Additional robustness testing is performed by considering incorrect modeling of domain shape. Main Results. The CGO-based methods are fast, and show strong robustness to incorrect domain modeling comparable to classic difference EIT imaging and fewer boundary artefacts than the TV regularized non-linear least squares reference reconstructions. Significance. This work is the first to demonstrate fully 3D CGO-based absolute EIT reconstruction on experimental data and also compares to TV-regularized absolute reconstruction. The speed (1–5 s) and quality of the reconstructions is encouraging for future work in absolute EIT.